Keeping an eye on the future and staying ahead of the game: A conceptual model of team proactive adaptation - Gevers, J.; Van der Haar, S.; Burtscher, M.; Marques-Quinteiro, P.; Santos, C. M.; Passos, A. M.; Uitdewilligen, S. (11th INGroup Annual Conference, 2016)
We describe the processes involved in a team’s collective, proactive response to prospected circumstances in an attempt to alter the course of current and future events or reduce their impact on the team’s (future) functioning, and explicate how these processes contribute to proficient and sustainable team functioning in turbulent environments.